2013
DOI: 10.1017/dmp.2013.42
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Health Impacts of the 2011 Summer Floods in Brisbane

Abstract: The 2011 Brisbane floods had significant impact on the physical and psychosocial health of residents. Improved support strategies may need to be integrated into existing disaster management programs to reduce flood-related health impacts, particularly those related to mental health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
52
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(58 citation statements)
references
References 24 publications
3
52
0
3
Order By: Relevance
“…Many epidemiology studies on the health impacts of floods use self-reporting methods to reconstruct flood events. [27][28][29] Some combine surveillance data with surveys. 30 These types of study designs can introduce recall and reporting bias.…”
Section: Discussionmentioning
confidence: 99%
“…Many epidemiology studies on the health impacts of floods use self-reporting methods to reconstruct flood events. [27][28][29] Some combine surveillance data with surveys. 30 These types of study designs can introduce recall and reporting bias.…”
Section: Discussionmentioning
confidence: 99%
“…It has been perceived as a challenge to humans because of its association with various undesirable environmental changes . Sustained alteration of climate results in elevated temperature and sea levels, alteration in humidity, and occurrence of unusual weather events like extreme precipitation . These changes contribute to the increase in severity and frequency of flooding …”
Section: Introductionmentioning
confidence: 99%
“…This is consistent with studies in the UK and Australia that found associations between flooding and psychological distress, anxiety and sleep quality. 12,13 However, it differs from an Australian study that showed a decrease in prescriptions of anti-anxiety medications immediately after a cyclone but an increase over a six-month period. 16 A possible explanation is that this Australian study looked at overall rates of prescriptions, whereas the current study looked at new prescriptions among individuals who had not had a previous prescription in the preceding year, and this specificity allowed for the detection of a signal.…”
Section: Mental Health and Violencementioning
confidence: 65%
“…11 Mental health impacts can include anxiety 12 and difficulty sleeping, 13 as well as the precipitation or exacerbation of mental health disorders requiring medical attention (e.g., depression, posttraumatic stress disorder). 11 For only a small subset of those with psychological distress will mental disorders go on to develop over the long term.…”
mentioning
confidence: 99%